Analysis Profitability of Capital Structure in Companies Manufacturing - Saprudin; Arman (International Journal of Management Progress, 2023)
The aim of this research is to determine and analyze the influence of capital structure (DER, DAR and CR) on profitability (ROE) in metal and similar subsector manufacturing companies listed on the Indonesia Stock Exchange. The data in this research is secondary data in the form of annual financial reports of metal companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2020 period obtained through the official BEI website. This research uses descriptive analysis methods and multiple linear regression analysis. The results of this research are: 1) Debt to Equity Ratio (DER) has a significant effect on Return on Equity (ROE) in a negative direction; 2) Debt to Asset Ratio (DAR) has no effect on Return on Equity (ROE); 3) Current Ratio (CR) influences Return on Equity (ROE) in a negative direction; 4) Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Current Ratio (CR) simultaneously have a positive effect on profitability as measured by Return on Equity (ROE).